ZnC3-2D a new material for hydrogen reversible storage predicted by first-principles calculations. (June 2022) - Labrousse, J.; Belasfar, K.; Aziz, O.; El Kenz, A.; Benyoussef, A.
Abstract: In order to improve the transport, electronics and storage properties of graphene layers, we have constructed compact structures with graphene sheets. With the Use of the density functional theory (DFT) and ab-initio molecular dynamics (AIMD) calculations including van der Waals interactions, the structural stability and hydrogen storage properties of the neat ZnC3 monolayer have been systematically investigated, the adsorption of H2 molecules on ZnC3 shows good results. A high binding energy up to 0.3169 eV with 3.30 Å as equilibrium distance. A low activation energy allows the molecule to migrate on the surface so easily up to 0.022 eV. The investigation revealed a high gravimetric (GC) and volumetric (Vc ) capacities up to 7.73 wt% and 98.44 g/l as a new 2D material for hydrogen storage. The hydrogenation/dehydrogenation (desorption) temperature is expected to be 215.55 K. The desorption temperature (TD ) proved to be significantly greater as compared to the critical point of hydrogen (33 K). Furthermore, the TD calculations were confirmed with AIMD simulations of the adsorption of 17 H2 molecule on ZnC3 . Thus, the monolayer ZnC3 could function as a reversible hydrogen storage substrate under feasible conditions. Graphical Abstract: ga1